2001
DOI: 10.1161/01.hyp.37.2.744
|View full text |Cite
|
Sign up to set email alerts
|

Workshop: Endothelial Cell Dysfunction Leading to Diabetic Nephropathy

Abstract: Abstract-Clinical manifestations of diabetic nephropathy are an expression of diabetic microangiopathy. This review revisits the previously proposed Steno hypothesis and advances our hypothesis that development of endothelial cell dysfunction represents a common pathophysiological pathway of diabetic complications. Specifically, the ability of glucose to scavenge nitric oxide is proposed as the initiation phase of endothelial dysfunction. Gradual accumulation of advanced glycated end products and induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
83
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 42 publications
4
83
0
3
Order By: Relevance
“…[63][64][65][66][67][68][69][70][71] The protein leakage in diabetic hypertensive patients has been attributed to endothelial dysfunction, which is present in both diabetes and hypertension. 72 Microalbuminuria in type II diabetic, 73 or nondiabetic hypertensive 74 patients has been associated, besides renal failure, with cardiovascular complications. The latter study 74 showed that for every 10-fold increase in the urinary albumin-creatinine ratio, the composite end point (death, MI or stroke) was increased by 57%, cardiovascular mortality by 97.7%, all cause mortality by 75.2%, stroke by 51% and MI by 45%.…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…[63][64][65][66][67][68][69][70][71] The protein leakage in diabetic hypertensive patients has been attributed to endothelial dysfunction, which is present in both diabetes and hypertension. 72 Microalbuminuria in type II diabetic, 73 or nondiabetic hypertensive 74 patients has been associated, besides renal failure, with cardiovascular complications. The latter study 74 showed that for every 10-fold increase in the urinary albumin-creatinine ratio, the composite end point (death, MI or stroke) was increased by 57%, cardiovascular mortality by 97.7%, all cause mortality by 75.2%, stroke by 51% and MI by 45%.…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…Chronic vascular adaptations could contribute to the preservation of renal function during acute exercise and confer renoprotective effects in diseases where endothelial function is compromised. This effect could be clinically relevant because renal pathophysiological processes resulting from hypercholesterolemia (49) as well as diabetic (13) and hypertensive (55) nephropathies have been associated with dysfunction of the renal vascular endothelium.…”
Section: Exercise Training and Renal Vascular Reactivitymentioning
confidence: 99%
“…EDHF seems to be essentially involved in the local regulation of blood flow in small resistance vessels (10,37), with the exception of the coronary and renal vascular beds where it also contributes to the modulation of vascular reactivity in conduit arteries (3). Endothelium dysfunction, which can be evidenced by an impairment in endothelium-dependent relaxation, plays a pivotal role in the pathogenesis of cardiovascular diseases, such as arterial hypertension and coronary heart disease (54), as well as in diabetic angiopathy (13). Moreover, NO interferes with key events involved in the development of atherosclerosis, such as smooth muscle cell proliferation, platelet adhesion and vessel wall interaction, and monocyte and leucocyte adhesion (54).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial dysfunction is associated with decreased NO availability, either through loss of NO production or through loss of NO biological activity [60]. NO production is diminished in cells which are subject to oxidative stress.…”
Section: Diabetic Nephropathy and Vascular Endothelial Dysfunctionmentioning
confidence: 99%